BS EN 55016-1-4 AMD2. Specification for radio disturbance and immunity measuring apparatus and methods. Part 1-4. Radio disturbance and immunity measuring apparatus. Antennas and test sites for radiated disturbance measurements (18th September 2020) - British Standards Institution,
No abstract available